FOSTERING ECOLOGICAL AWARENESS: THE ROLE OF ECOTHEOLOGY-BASED ISLAMIC EDUCATION IN HIGHER EDUCATION - Titi Kadi; Badrut Tamam (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to explore the integration of ecotheology into Islamic Religious Education (PAI) in higher education and its impact on strengthening students' ecological awareness. In Indonesia, the environmental crisis, driven by unchecked exploitation of natural resources, has become a pressing issue, and Islamic Religious Education plays a key role in shaping students’ attitudes toward environmental responsibility. A qualitative interpretive approach was adopted, employing a multisite design at universities. The research findings reveal that the curriculum integrates ecotheological values, with a focus on human dignity, ethical responsibility, and environmental stewardship. The learning process emphasizes active learning strategies, such as project- and problem-based learning, encouraging students to apply Islamic values to real-world environmental issues. The evaluation methods include diagnostic, formative, and summative assessments to measure students’ ecological knowledge and behavior. The study contributes to bridging religious education and ecological sustainability, proposing the need for more comprehensive curriculum reforms, faculty training, and policy support. Future research should expand to include more institutions and assess long-term behavioral impacts.